DESIGN OF ROTARY GRIPPER STATION FOR MODULAR MECHATRONICS SYSTEMS AT POLMAN ASTRA - Syahril Ardi; M Hidayat; Irfandaresa Sangun (Technologic, 2011)
Developing to modular mechatronics system has been a need for complementary mechatronics learning system at Politeknik Manufaktur Astra. The system is a whole and integration in the conveyor belt system. We design a rotary gripper station that can be used for lifting work-object by gripping it with the vacuum. After work-object has been gripped, then shift it to the next station. In this paper, we design a rotary actuator as an actuator tool that can move by rotary until 1800. Based on the design results, calculation analysis, and testing this equipment, has been getting that the equipment specification as the same with the needs.